Analysis of the Connection Level Technological Expenditures of Common WLAN Models - Kajackas, A.; Pavilanskas, L. (Elektronika ir Elektrotechnika, 2007)
The investigation of technological expenditures and redundancy in WLAN of IEEE 802.11 standard presented in [8] is preceded. The analysis is extended to connection level of infrastructure networks by fitting them for transmission of real time signals. As known, in packet formation process for each data block transmitted over WLAN the headers of different protocols are appended. By fit allocation of the transmission times the additional time intervals are inserted too. The headers of packets and the additional time intervals increase the technological expenditures and the time of channel occupation. In proceeding, the real time expenditures calculated by reference to conversational speech model, specified in ITU P.59. The result of the presented task is realistically calculated expenditures of WLAN when the high quality telephony services are provided. This enable to determine intended for real time communications, general capacity of the channel. Ill. 7, bibl. 10 (in English; abstracts in English, Russian and Lithuanian).